Machine gun prayer: the politics of embodied desire in Pentecostal worship - Richman, N (Taylor and Francis, 2020)
This article examines Pentecostal embodiment through a study of the way prayer is spoken of and performed in a prominent Nigerian Deliverance church. It argues that the Deliverance churches’ exaggerated emphasis on the demonic serves to re-purpose prayer as an embodied violent performance that is often as much directed to the devil as it is to God. This article thus reveals the ways in which the entanglement of divine and demonic beings in the Pentecostal body results in the production of a subject that does not just act upon itself, but in fact seeks to defeat and hence deliver itself. Moreover, in offering a detailed account of how the movement’s theology of the body is made manifest in performances of prayer, the article argues for scholarly attention to the role that theological doctrines play in the constitution of embodied experience in the study of religions more generally.